Clostridium butyricum, a future star in sepsis treatment - Zhao, Jinglin; Jiang, Li; He, Weizhi; Han, Dingrui; Yang, Xuan; Wu, Liuli; Zhong, Haiyan (Frontiers in Cellular and Infection Microbiology, 2024)
Sepsis is a systemic inflammatory response syndrome of multiorgan failure caused by dysregulation of the host response to infection and is a major cause of death in critically ill patients. In recent years, with the continuous development of sequencing technology, the intestinal microecology of this disease has been increasingly studied. The gut microbiota plays a host-protective role mainly through the maintenance of normal immune function and the intestinal barrier. Recent evidence suggests that intestinal flora dysbiosis plays a crucial role in sepsis. Clostridium butyricum (C. butyricum), which has been used as a probiotic in poultry feed since its discovery, has been found to play a potential protective role in intestinal infections, inflammatory bowel disease (IBD), colorectal cancer, and other diseases in recent studies. In this review, we continue to focus on the important role and mechanism of C. butyricum as a probiotic in human diseases, especially intestinal diseases. Additionally, we evaluate the research progress of C. butyricum in treatment of sepsis to identify more therapeutic targets for the clinical treatment of sepsis.